New Ways to Write the History of Western Europe and the United States: The Concept of Intercultural Transfer. Issue 10 (6th October 2013) - Adam, Thomas
Abstract The concept of intercultural transfer was originally developed in the 1980s for the study of exchange processes between France and Germany in the time of the Enlightenment and the French Revolution. More recently, various scholars have applied it to the exchange processes across the Atlantic (and between Germany and the United States in particular) and across the British Chanel (and between Germany and Great Britain in particular). Its focus is cultural transformation, since the transferred elements reflect the influence of the agents of intercultural transfer as well as both the giving and the receiving society. This paper seeks to provide an alternative to traditional accounts of German and American history by highlighting transfers that occurred in the realm of culture, education, and customs in the 19th century. Such transfer included concepts for the organization of the urban infrastructure of American cities (from museums and schools to city parks) as well as models for education (from kindergarten to university). Both cultures and societies were deeply connected by these cultural transfers even though they occurred outside the realm of state action and apart from the increasing control of both nation states over the movement of its citizens within civil society. Intercultural transfers were organized and carried out by agents of intercultural transfer. These agents were private citizens who acted on their own initiative as agents of civil society but not as agents of nation states. The development of German and American society and culture in the 19th century was, thus, intrinsically linked and resulted in a multitude of cross‐cultural interconnections that contributed to the diversification of both societies. The Atlantic represented in this narrative a "connective lifeline" rather than a separating gulf.